2022
DOI: 10.3389/fpubh.2022.903747
|View full text |Cite
|
Sign up to set email alerts
|

HCV Self-Testing to Expand Testing: A Pilot Among Men Who Have Sex With Men in China

Abstract: BackgroundHepatitis C virus self-testing (HCVST) may increase test uptake especially among marginalized key populations such as men who have sex with men (MSM). We conducted an observational study to assess the usability, acceptability and feasibility of HCVST among MSM in China.MethodsAn observational study with convenience sampling was performed among MSM in Guangzhou, China in 2019. The OraQuick® HCV Rapid Antibody Test kits were used in this study. Participants performed all 12 HCVST steps and interpreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Finally, screening and full‐text assessment resulted in six included manuscripts comprising 870 individuals from six countries (United States of America [ n = 95 people with chronic liver diseases], Kenya [ n = 150 PWID], Egypt [ n = 116 participants from the general population], Vietnam [ n = 104 MSM and n = 105 PWID], China [ n = 100 MSM] and Georgia [ n = 100 MSM and n = 100 PWID]) (Figure 1). 20–25 All studies were published in English and used OraQuick® HCV Rapid Antibody Test (OraSure Technologies Inc). HCVST results were checked by a healthcare provider in all studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, screening and full‐text assessment resulted in six included manuscripts comprising 870 individuals from six countries (United States of America [ n = 95 people with chronic liver diseases], Kenya [ n = 150 PWID], Egypt [ n = 116 participants from the general population], Vietnam [ n = 104 MSM and n = 105 PWID], China [ n = 100 MSM] and Georgia [ n = 100 MSM and n = 100 PWID]) (Figure 1). 20–25 All studies were published in English and used OraQuick® HCV Rapid Antibody Test (OraSure Technologies Inc). HCVST results were checked by a healthcare provider in all studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is expected a decrease of HCVST kits price due to the competition on the pipeline of WHO pre‐qualification. A cost‐effectiveness analysis (CEA) using data from those publications from China, 24 Georgia, 25 Vietnam 22 and Kenya 23 was reported in the WHO guideline (Web Annex F—https://www.who.int/publications/i/item/9789240031128). The cost per HCV diagnosis by the standard‐of‐care was extremely variable among those countries (from US$ 35 in Vietnam to US$ 361 in Kenya).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are currently no tests approved for HCV self-testing by WHO prequalification or other stringent regulatory authorities, several quality-assured tests are in the pipeline. To adapt and introduce self-testing for HCV, in 2019, the Foundation for Innovative New Diagnostics (FIND), in collaboration with WHO, conducted a series of pilot studies of HCV self-testing in Egypt [ 25 ], Vietnam [ 26 ], Georgia, Kenya, and China [ 27 ], which showed a high usability, acceptability and feasibility of using HCV self-testing among MSM. The pilot study in China showed that 76.0% (95% CI: 66.4 to 84.0%) of MSM found HCV self-testing acceptable [ 27 ].…”
Section: Introductionmentioning
confidence: 99%